A FAK Inhibitor Boosts Anti-PD1 Immunotherapy in a Hepatocellular Carcinoma Mouse Model - Wei, Yuhua; Wang, Yufeng; Liu, Nanbin; Qi, Ran; Xu, Yan; Li, Kun; Feng, Yu; Shi, Baomin (Frontiers in Pharmacology, 2022)
Anti-PD-1/PD-L1 immunotherapy in hepatocellular carcinoma (HCC) only benefits some patients, much poorer efficacy than other tumors. A FAK inhibitor (VS-4718) has been reported to improve the microenvironment in some tumors. This study aimed to investigate the effect of the combination of FAK inhibitor (VS4718) and anti-PD1 for the treatment of HCC in a mouse model and its possible mechanism of action. Then, the expression of FAK and infiltrated immune cells in human HCC from the data of TCGA were analyzed. A primary murine HCC model was established via protooncogene (c-Met/β-catenin) transfection. The pathological characteristics were examined after the mice were treated with VS4718 and/or anti-PD1 therapy. This study revealed that FAK is highly expressed in human HCC and is associated with poor prognosis of OS (overall survival) and PFS (progress free survival) in HCC patients. Immune cell infiltration (CD8+ T, Tregs, M0, M2, CAFs and MDSCs) was correlated with FAK expression. In the experimental HCC model, the combination of a FAK inhibitor (VS4718) and an anti-PD1 antibody had a better effect than monotherapy against HCC. VS4718 reduced the number of Tregs and macrophages but increased the number of CD8+ T cells in HCC mice. Notably, FAK inhibitor promoted the expression of PD-L1 in HCC. This study suggested that combination of a FAK inhibitor (VS4718) and anti-PD1 could be a potential therapy for HCC by improving the immune environment, reducing liver fibrosis and simultaneously preventing PD1 from binding to the increased PD-L1 induced by FAK inhibitor (VS4718).